The vulnerability of refugees and asylum seekers in Italy: Insights from a nationwide survey - Daria Mendola; Eralba Cela; Livia Elisa Ortensi; Maurizio Ambrosini; Micaela Arcaio; Elisa Barbiano di Belgiojoso; Annalisa Busetta; Roberto Impicciatore; Eleonora Miaci; Marta Parigi; Anna Maria Parroco; Manuela Stranges; et al. (PLoS ONE, 2026)
Despite the high number of news articles, images and public debate on forcibly displaced individuals, there is, with some rare exceptions, a lack of comprehensive surveys on their living conditions. In this context, our paper contributes to filling part of this gap by presenting the results of a new survey conducted in Italy in 2024 in the framework of the AVRAI research program. The survey collected responses from 1,327 adults with international protection or a history of seeking asylum, who arrived in Italy after 2011. This paper describes the main dimensions of vulnerability, offering insights on existing disparities based on gender and area of origin. Our survey reveals legal uncertainty, especially common among newcomers from Bangladesh, Pakistan and MENA countries. Health data shows that self-rated physical health is generally good but mental health outcomes are poorer, particularly among women, recent arrivals and those from Central and the Horn of Africa. Women also face greater employment challenges. Economic hardship is widespread, with over one-third experiencing severe material deprivation and high food insecurity, especially among Nigerians, Sub-Saharan Africans and MENA nationals. Despite adversities, many respondents show strong resilience, particularly those with higher education and coming from Sub-Saharan Africa and the Horn of Africa. About two thirds of respondents plan to remain in Italy and nearly two thirds feel welcome in Italy. However, discrimination and racism, especially against individuals of African origin, remain a significant concern. Although many express their satisfaction with life in Italy, experiences of exclusion are common. This survey sheds light on legal precarity, health risks, economic vulnerability, living conditions and lived experiences and perceptions in the peculiar Italian political, legal and administrative environment.